2022
DOI: 10.51872/prjah.vol4.iss1.177
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Exploration of Street Children Life in Peshawar, Khyber Pakhtunkhwa in the light of Urie Bronfenbrenner's Ecological Systems Theory

Abstract: The number of street children is increasing at alarming rate in the country. The several composite factors drive these children to the street life where they are confronted with the numerous threats. This study proposed to explore the root causes alongside the risks connected with street life. A qualitative study design was used to interview 50 street children from 5 hotspot sites of Peshawar, which includes Haji Camp Adda, Gulbahar, Karhano Market, University Town and Firdous Bazaar. This study is based on Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The findings indicated that street children's lack of access to formal education hinders their attainment of a higher social and economic status in life. Ashraf et al (2022) note that poverty is inevitable among street children, because they lack fundamental social services such as education and health care, vital to attaining a better living standard. The mesosystem of the ESA highlights the importance of schooling in child development.…”
Section: Discussion Of Risks and Implications For Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that street children's lack of access to formal education hinders their attainment of a higher social and economic status in life. Ashraf et al (2022) note that poverty is inevitable among street children, because they lack fundamental social services such as education and health care, vital to attaining a better living standard. The mesosystem of the ESA highlights the importance of schooling in child development.…”
Section: Discussion Of Risks and Implications For Practicementioning
confidence: 99%
“…In this study the questionnaire was structured to gather relevant data to assess the children and to make recommendations for developmental social work interventions. Furthermore, psychosocial and developmental interventions implemented by social workers are crucial to address the numerous deprivations faced by street children (Ashraf, Ibrar & Ullah, 2022). The ESA guides social work practice in Zimbabwe in formulating family tracing and family reunification programmes, which are vital in reducing the number of children on the streets.…”
Section: Synthesis Of the Ecological Approach And Developmental Socia...mentioning
confidence: 99%